Membangun Corporate Branding yang berkelanjutan di Era Kecerdasan Buatan : Peran Corporate Social Responsibility dan Komunikasi Perusahaan - Denpharanto Agung Krisprimandoyo (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the relationship between corporate communication, artificial intelligence (AI), corporate social responsibility (CSR), and the formation of sustainable corporate branding. The research method used is case analysis and empirical data to understand how AI can improve a company's communication and CSR strategies. The research results show that the use of AI in communication and CSR can strengthen brand identity and support the building of a lasting corporate brand. The conclusion is that the integration of company values with AI-driven processes and appropriate communications is critical in creating and maintaining a meaningful company brand that can connect with modern consumers and endure over time. Keywords : Corporate Branding, Artificial Intelligence, Role of CSR